Women, faith, and authority: Malama Zainab Ja'afar and the navigation of religious authority in Northern Nigeria - Nasir, Muhammad Muhammad; Noor, Haula (ATTARBIYAH: Journal of Islamic Culture and Education, 2023)
This research examines female religious authority in northern Nigeria, with a specific emphasis on Malama Zainab Ja'afar Mahmood Adam. The research investigates how Malama Zainab negotiates her authority amidst controversies surrounding her public presence as a preacher and Qur'anic exegete within the male dominated Izala movement, a prominent reform movement with widespread influence throughout West Africa and beyond. Employing a qualitative approach, the study delves into Malama Zainab's background, social capital development, and association with Izala, utilizing both secondary sources and indepth interviews with her. The findings highlight Malama Zainab's efforts in bringing women to the forefront within mosque spaces and other gender-segregated settings, fostering their religious participation publicly. While her public activities primarily target female audiences, her preaching and proselytizing reach males through social media platforms, expanding her influence beyond traditional boundaries. Importantly, the findings also shed light on how the historical exclusion of women in socio-religious spaces in northern Nigeria is based on cultural and traditional interpretations rather than explicit religious prohibitions. Hence, the research contributes to the broader understanding of female religious authority, shedding light on the under-recognition of female scholars in comparison to their male counterparts in many Muslim-majority countries.